Cover Feature: Single‐Site Ruthenium Pincer Complex Knitted into Porous Organic Polymers for Dehydrogenation of Formic Acid (ChemSusChem 20/2018). Issue 20 (23rd October 2018) - Wang, Xinbo; Ling, Eleanor Ang Pei; Guan, Chao; Zhang, Qinggang; Wu, Wenting; Liu, Pengxin; Zheng, Nanfeng; Zhang, Daliang; Lopatin, Sergei; Lai, Zhiping; Huang, Kuo‐Wei
Abstract : The Cover Feature shows a single‐site ruthenium pincer complex that is knitted into porous organic polymers. In their Full Paper, X. Wang et al. prepared a new heterogeneous ruthenium pincer framework with single‐atomic sites in one step by the direct knitting of a PN 3 P‐pincer ruthenium complex in a porous organic polymer. More information can be found in the Full Paper by X. Wang et al. on page 3591 in Issue 20, 2018 (DOI: 10.1002/cssc.201801980 ).